Negative refraction & super resolution imaging in hyperbolic metamaterials - Tan, Lenny Yan Zhong (2019)
In this final year report, the main discussions will be related to negative refractive index, whereby the phenomenon of negative refraction can be achieved through various methods such as NIM and HMM. More importantly, this project investigates the means of using hyperlens to obtain super-resolution imaging and the possible design to improve the structure of it. Software such as MATLAB and Comsol Multiphysics 5.3a were utilized to facilitate the experiments of this project, where simulations of various models that implemented the theory of negative refraction were presented. Last but not the least, conclusion and future work recommendations were included in this report as well.